Antioxidant and pro-apoptosis activities of coffee husk (Coffea arabica) anthocyanins - Yin, X. (2024)
The commercial use of coffee (Coffea arabica) husks, one of the major solid residues obtained during the dry processing of coffee, has previously been considered unprofitable. However, coffee husks are an excellent source of stable anthocyanins that have antioxidative, anti-inflammatory, and cardioprotective properties. The present work identified two anthocyanins, cyanidin-3-glucoside and cyanidin-3-rutinoside, from coffee husks by high-performance liquid chromatography and liquid chromatography-mass spectrometry. The antioxidant capabilities were tested by quenching free radical scavenge assay, reducing power, and ORAC assay at 50, 100, 150, 200 mg/L of coffee husk anthocyanins (CHAs). Moreover, the effects of different concentrations of CHAs on superoxide dismutase (SOD) and lactate acid dehydrogenase (LDH), and the concentration of malondialdehyde (MDA) in human umbilical vein endothelial cells exposed to hydrogen peroxide were also evaluated. Human colon cancer (Caco-2) cell apoptosis induced by CHAs was examined by flow cytometry. Based on the results, CHAs showed strong dose-dependent antioxidant activities, and could increase SOD activity, and suppress indicators for oxidative injuries such as MDA and LDH. Furthermore, the proportion of apoptotic Caco-2 cells ranged from 4.12 to 41.3% in response to treatment with different concentrations of CHAs. These results suggest that CHAs exhibit antioxidant and pro-apoptosis activities.